SISTEM INFORMASI PEMESANAN BARANG PADA BENGKEL TAWAKKAL JAYA BERBASIS WEB - Rusdiana, Lili; Sugianoor, Dhehen; Rosmiati, Rosmiati (SINTECH (Science and Information Technology) Journal, 2018)
The Tawakal Jaya workshop previously used paper for data recording, goods ordering transaction, and promotion. This results in the manual system less efficient in saving time. Therefore it is necessary to design and development of Information Systems Ordering Goods Based Website at Workshop "Tawakal Jaya". The system is designed using context diagrams and data flow diagrams, while system development uses PHP programming language. System development method using Extreme Programming method which is a group of agile methods. The built system can be accessed online and then done the questionnaire so that it can be obtained that the use of the system can be accepted by the user due to time savings in processing data and transact in ordering goods.